(untitled) - Jack C. Richards (Oxford, 2003)
This title features: recordings that reflect everyday situations; follow-up listening and speaking activities; 'Over to You' sections for extra speaking practice; a student audio CD for practice outside the classroom; photocopiable speaking activities for each unit; and mid-term, final, and unit tests with audio CDs for easy student assessment.
Nghe và Nói 1 (*)
Keywords: English language; Spoken english